Plan de negocio para la creación de una empresa de marketing digital, cantón Quevedo, año 2014 - Miranda Cruz, Cristhian Enrique (2015)
The Quevedo Canton is in the need to acquire specialized services Marketing Online advertising agencies or also known as (Digital Marketing) that meet the needs of companies with high added value. Normally the different companies operating in the canton of Quevedo not have a department devoted to providing these services, noting that companies are part of these services do not have a specific prototype to provide digital advertising, so the target primary market is evaluated Quevedo on a business plan for the creation of a digital marketing company to determine your claim. The latest project is a marketing tool to use and provides solutions to companies when designing organize and Internet advertising favoring the retention and recruitment of potential customers so they can advertise and sell products and services offered by companies enthusiasts advertising through digital media. The company name is "artdigital" Marketing & advertising services which sell their services to the business population of the canton Quevedo - Los Ríos Province, established in the aforementioned city. According to the general objective of the research, Situational Analysis; Mission, Vision, Goals and Policies, Budget, would begin the financial study released since the economic viability of the project, with an investment of $ 50,000 60320.19 these will be financed by a loan from the Development Bank with an interest of 11% , for a period of 5 years annual $ 13.528.52, an investment of $ 20,000, they would themselves which would have an NPV = $ 155,251.95, a TIR of 57% and a recovery time of 2 years, 17 days, with a balance in units of 100 consultants annually. It is concluded that the project is a viable alternative production, thus raising its performance to ensure profitability, following the proposal presented in this research project.